ANALISIS MODEL KOMUNIKASI HAROLD DWIGHT LASWELL TERHADAP NOVEL ASMA NADIA CINTA 2 KODI - fahma, al Himni; halimah, Nur (Institut Agama Islam Syarifuddin Lumajang, 2018)
This study discusses the application of Harold Dwight Laswell's communication model on  Asma  Nadia?s  Cinta  2  Kodi.  By  applying  it,  the  author  only  uses  the  message elements.   The   author   has   classified   several   communication   messages   including: patriarchal and matriarchal culture, maternal affection over father, wife's obedience to  husband  due  to  compulsion,  husband's  advice  to  wife,  da'wah  and  the  main character  (Kartika  or  communicant).  The  results  of  this  study  by  applying  Harold Dwight  Laswell's  communication  model  on  Asma  Nadia?s  Cinta  2  Kodi  showsthe messages and the effects. Based on the results of the study, it can be concluded that there  are  five  elements  of  Laswell?s  communication  model:  Communicators  (who), Message (says  what),  receiver  (to  whom),  Medium  (in  which  channel),  Effect  (with what effect). Key Words: Communication Model, Messages, Effects of Communication